Ethically we can no longer sit on the fence? - Patricios, J (South African Journal of Sports Medicine, 2007)
To the Editor: We would like to comment on the review article by Shuttleworth-Edwards et al. ’Ethically we can no longer sit on the fence – a neuropsychological perspective on the cerebrally hazardous contact sports’, published in the July edition of your Journal.